Mindfulness and performance - Baltzell, Amy (Cambridge : Cambridge University Press, 2016)
Incorporating the theoretical conceptualizations of Jon Kabat-Zinn and Ellen Langer, this volume illustrates how performers from a variety of disciplines - including sport, dance and music - can use mindfulness to achieve peak performance and improve personal well-being. Leading scholars in the field present cutting-edge research and outline their unique approach to mindfulness that is supported by both theory and practice. They provide an overview of current mindfulness-based manuals and programs used around the globe in countries such as the United States, China and Australia, exploring their effectiveness across cultures. Mindfulness and Performance will be a beneficial reference for practitioners, social and sport psychologists, coaches, athletes, teachers and students.
Title from publisher's bibliographic system (viewed on 07 Jan 2016).
Keywords: Mindfulness (Psychology); Meditation -- Therapeutic use; Performance -- Psychological aspects